2006
DOI: 10.1097/01.mpg.0000229550.54455.63
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Gastrostomy in Children: A Safe Technique with Major Symptom Relief and High Parental Satisfaction

Abstract: PEG is a safe technique for establishing enteral feeding, even in very sick children. Major complications are rare, although most children experience minor stoma-related problems. Parents/caregivers report that the gastrostomy is of great help for themselves and their child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
80
4
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 33 publications
15
80
4
7
Order By: Relevance
“…While the majority of parents resisted to placement of PEG initially, most of them were satisfied with the outcome (21). In the study of Avitslan et al (23) in which 121 children who had a PEG catheter were evaluated retrospectively, 98% of the parents reported that they could again decide to let their children have a PEG catheter placed. Similarly, positive answers were obtained in our study when the parents were asked if they would let their children have a PEG catheter placed if they had to decide again.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of parents resisted to placement of PEG initially, most of them were satisfied with the outcome (21). In the study of Avitslan et al (23) in which 121 children who had a PEG catheter were evaluated retrospectively, 98% of the parents reported that they could again decide to let their children have a PEG catheter placed. Similarly, positive answers were obtained in our study when the parents were asked if they would let their children have a PEG catheter placed if they had to decide again.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies investigating the acceptibility of percutaneous endoscopic nutrition by parents have been conducted (21)(22)(23). While the majority of parents resisted to placement of PEG initially, most of them were satisfied with the outcome (21).…”
Section: Discussionmentioning
confidence: 99%
“…2 As complicações da PEG são relativamente frequentes, podendo atingir taxas de 8-30%; em séries com seguimento longo, a taxa de complicações pode mesmo chegar aos 73%. 2,20,21 As complicações major (peritonite, hemorragia, lesão visceral) são, contudo, excecionais mas não desprezíveis. [20][21][22][23][24][25] A incidência de infeção local do ostoma pode ser significativamente diminuída pela antibioprofilaxia.…”
Section: Gastrostomiasunclassified
“…The procedure takes place either in the endoscopic or operating room, sometimes in the Intensive Care Unit. The most common indications include sucking, chewing and swallowing disturbances in children with neurological disorders such as cerebral palsy, hypoxic-ischaemic encephalopathy, and spinal muscular atrophy [3].…”
Section: Introductionmentioning
confidence: 99%